Management of Buerger's Disease in Endovascular Era - Ghoneim, Baker M.; Karmota, Ahmed G.; Abuhadema, Ahmed M.; Shaker, Ahmed A.; Abdelmawla, Hany M.; Nasser, Mahmoud M.; Elmahdy, Hossam Y.; Mostafa, Hesham A.; Khairy, Hussein M. (International Journal of Angiology, 2019)
This study was aimed to report data on the feasibility, safety, and effectiveness of endovascular procedures in a thromboangiitis obliterans diagnosed patients presenting with critical limb ischemia (CLI). Prospective study conducted on patients affected by Buerger's disease who presented to our center along 2 years. Clinical, radiological, and patient-based outcomes were recorded at 3, 6, and 12 months after the intervention. Total 39 patients were included in the study. Fifteen (38.5%) patients underwent percutaneous transluminal angioplasty, another 15 patients (38.5%) underwent follow-up on medical treatment, there are four other patients (10.3%) underwent surgical bypass, and five (12.8%) patients underwent lumbar sympathectomy. The 12 months' outcome showed 66.7% technical success in endovascular group with 46.7% patency rate (p-value = 0.06), 86.7% limb salvage rate (LSR; p-value < 0.04), and 66.7% clinical improvement (p-value = 0.005). The endovascular management of Buerger's disease is feasible, save, and effective with high rate of LSR and clinical improvement.
Keywords: angioplasty; arteritis; Buerger's disease; catheter-directed; thrombolysis; critical limb ischemia; endovascular procedure; nicotine